Epigenetically active chromatin in neonatal iWAT reveals GABPα as a potential regulator of beige adipogenesis - Mooli, Raja Gopal Reddy; Zhu, Bokai; Khan, Saifur R.; Nagati, Veerababu; Michealraj, Kulandaimanuvel Antony; Jurczak, Michael J.; Ramakrishnan, Sadeesh K. (Frontiers in Endocrinology, 2024)
Background: Thermogenic beige adipocytes, which dissipate energy as heat, are found in neonates and adults. Recent studies show neonatal beige adipocytes are highly plastic and contribute to >50% of beige adipocytes in adults. Neonatal beige adipocytes are distinct from recruited beige adipocytes in that they develop independently of temperature and sympathetic innervation through poorly defined mechanisms.We characterized the neonatal beige adipocytes in the inguinal white adipose tissue (iWAT) of C57BL6 mice postnatal day 3 and 20 mice (P3 and P20) by imaging, genome-wide RNA-seq analysis, ChIP-seq analysis, qRT-PCR validation, and biochemical assays.We found that an increase in acetylated histone 3 lysine 27 (H3K27ac) on the promoter and enhancer regions of beige-specific gene UCP1 in iWAT of P20 mice. Further, H3K27acChIP-seq analysis in the iWAT of P3 and P20 mice revealed strong H3K27ac signals at beige adipocyte-associated genes in the iWAT of P20 mice. The integration of H3K27ac ChIP-seq and RNA-seq analysis in the iWAT of P20 mice reveal epigenetically active signatures of beige adipocytes, including oxidative phosphorylation and mitochondrial metabolism. We identify the enrichment of GA-binding protein alpha (GABPa) binding regions in the epigenetically active chromatin regions of the P20 iWAT, particularly on beige genes, and demonstrate that GABPa is required for beige adipocyte differentiation. Moreover, transcriptomic analysis and glucose oxidation assays revealed increased glycolytic activity in the neonatal iWAT from P20.Our findings demonstrate that epigenetic mechanisms regulate the development of peri-weaning beige adipocytes via GABPa. Further studies to better understand the upstream mechanisms that regulate epigenetic activation of GABPa and characterization of the metabolic identity of neonatal beige adipocytes will help us harness their therapeutic potential in metabolic diseases.